Socialization of Self Medication in Elderly at Posyandu Cinta Lansia - Meilantika, Ayu Diana; Risky, Ayu; Nuruniyah, Nuruniyah; Mayarestya, Nita Putriasti; Masdah, Siti (Edumedia Solution, 2025)
The aging process is a natural process accompanied by a decline in physical, psychological, and social conditions that interact with each other. This condition tends to pose health problems for the elderly. The increasing tendency of pathological conditions in the elderly leads to increased medication consumption, thereby enlarging the risk of drugs related problems (DRPs), including side effects, drug interactions, or toxic reactions. The problems found are inappropriate drug use and a lack of understanding of how to use, store, and dispose of medicines correctly. Additionally, other issues include the inappropriate use of antibiotics among the elderly, caused by a lack of understanding and incorrect behavior in medication use. The purpose of this service is to socialize with the elderly about self-medication. The method used is counseling directed at the elderly. The results obtained from this service show that the elderly became more careful in self-medication.